Blue phosphorescent organic light-emitting devices based on carbazole/thioxanthene-S, S-dioxide with a high glass transition temperature. Issue 24 (28th June 2015) - Jeon, Young Pyo; Kim, Kyu Sung; Lee, Kyeong Kyun; Moon, In Kyu; Choo, Dong Chul; Lee, Jun Yeob; Kim, Tae Whan
<x xml:space="preserve">Abstract</x> A bipolar host material for blue organic light-emitting devices was synthesized by incorporating electron-donating carbazole and electron-accepting thioxanthene-S, S-dioxide into one molecule using a solventless green reaction.